RIPK3 impacts antibody generation in an induced model of murine lupus through mechanisms other than necroptosis and antigen presentation - Pilon, Céleste; Lonina, Elena; Levine, Jerrold S.; Lesage, Sylvie; Rauch, Joyce (Frontiers in Immunology, 2025)
IntroductionReceptor-interacting protein kinase 3 (RIPK3) is a protein involved in cell death and inflammatory processes. The most recognized function of RIPK3 is the induction of necroptosis, an inflammatory type of cell death that is dependent on RIPK3 kinase activity. Deficiency in RIPK3-dependent pathways has been associated with protection from various inflammatory and autoimmune conditions. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the generation of autoantibodies to multiple intracellular antigens leading to multi-organ pathology. Little is known about the involvement of RIPK3-dependent pathways in SLE. We have previously shown that autoantibody generation in an induced model of murine lupus is impaired in RIPK3-deficient mice. The current study aimed to identify the RIPK3-dependent mechanisms that contribute to autoantibody generation in this induced model of murine lupus.MethodsSLE was induced in C57BL/6 (wild type), RIPK3-/-, RIPK3K51A/K51A, and MLKL-/- mice by subcutaneous immunization with a mixture of β2-glycoprotein I and lipopolysaccharide in order to evaluate the contribution of RIPK3 and MLKL to autoantibody production in this model. Bone marrow chimeras were generated to investigate the impact of RIPK3 deficiency within the hematopoietic compartment. Antigen presentation assays assessed the impact of RIPK3 deficiency in antigen presenting cells on T cell activation in vitro. T cells were evaluated ex vivo by flow cytometry following the induction of SLE in wild type and RIPK3-dependent pathway-deficient mice.ResultsGeneration of autoantibodies to SLE antigens following immunization with β2-glycoprotein I and lipopolysaccharide was found to be dependent on RIPK3 activity, but independent of MLKL (i.e., RIPK3-dependent necroptosis). Bone marrow chimeric experiments revealed that RIPK3 mediates autoantibody generation through both immune and non-immune compartments. RIPK3 deficiency within antigen presenting cells did not impact T cell activation in vitro. Moreover, early and late T cell activation ex vivo was not impaired in RIPK3-deficient mice following induction of murine lupus.ConclusionThese results suggest that RIPK3 contributes to autoantibody generation in our induced model of murine lupus through an interplay of pathways that appear to be independent of necroptosis and antigen presentation.